ANALISIS PENGARUH MODAL MANUSIA, UMK DAN PDRB TERHADAP INVESTASI ASING LANGSUNG DI KABUPATEN/KOTA PROVINSI BALI - Malok, Angela Septiani Widya; Mahaendra Yasa, I Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
This study aims to analyze the effect of human capital, regency/city minimum wage and GRDP simultaneously and partially on FDI in regency/city of Bali Province. This research was conducted in the regency/city area of Bali Province with 9 years of observation in the period 2011 to 2019. The data used is secondary data, which is then analyzed descriptively and inferentially using multiple linear regression analysis. In this study, the panel data model that was chosen is Common Effect Model (CEM). The results showed that human capital, regency/city minimum wage and GRDP simultaneously had a significant effect on FDI in regency/city of Bali Province. In addition, it was also found that human capital and regency/city minimum wage partially have a negative and significant effect, while GRDP has a positive and significant effect on FDI in regency/city of Bali Province. The implication of this research that there is a need for commitment from various parties to be able to increase the entry of FDI in the regency/city of Bali Province through improving the quality of human capital, increasing the regency/city minimum wage followed by an increase in labor productivity, and through the availability of infrastructure that can support economic activities so that can increase regional output which is reflected in GRDP.